Faktor-Faktor Yang Mempengaruhi Firm Value Pada Perusahaan Manufaktur - Juan Felix, Henryanto Wijaya (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to analyze the effect of capital structure, firm size, dividend policy, and profitability variable to the firm value. Population on this research are manufacturing company listed one BEI from 2017 – 2019. Sampling technique in this research is using purposive sampling and 48 company within 3 years period and the result using 144 sample. To get the final result, researcher use Microsoft Excel 2013 and software Eviews 10 program to produce panel data regression. Result of this research show that capital structure not significant negative on firm value, firm size significant positive on firm value, dividend policy not significant positive on firm value, and profitability significant positive on firm value.